Disaggregated benders decomposition for solving a network maintenance scheduling problem. Issue 6 (3rd June 2019) - Pearce, Robin H.; Forbes, Michael
Abstract : We consider a problem concerning a network and a set of maintenance requests to be undertaken. The aim is to schedule the maintenance in such a way as to minimise the impact on the total throughput of the network. We embed disaggregated Benders decomposition in a branch-and-cut framework to solve the problem to optimality, as well as explore the strengths and weaknesses of the technique. We prove that our Benders cuts are Pareto-optimal. Solutions to the linear programming relaxation also provide further valid inequalities to reduce total solving time. We implement these techniques on simulated data presented in previous papers and compare our solution technique to previous methods and a direct mixed-integer programming formulation. We prove optimality in many problem instances that have not previously been proven.